A política de humanização no hospital universitário do oeste do paraná - Miglioranza, Dalas Cristina (2015)
This study proposes to discuss how it has been the implementation of the National Policy of Humanization (PNH), in a general public school hospital called Hospital Universitário do Oeste do Paraná (HUOP). It aimed to understand which main elements present in this organization has influenced the implementation process of the PNH. The PNH proposes to engage and enhance workers, managers and users, in order to qualify and cause changes in management and health care process through concrete and objective elements and valuing the subjective aspects of the labor relations in health services. The research appears as a case study, and as a methodological resource, it was adopted the documental research and conducting semi-structured interviews, which enabled the analysis from thematic groups. The PNH begins to be thought in the HUOP from the contracting process for the achievement of goals and financial transfers. Therefore, it was necessary to create a Working Humanization Group (GTH), named as Humanization Commission (CH), and this has become the space responsible for humanizing actions in this service. It is noteworthy that some provisions of PNH have been deployed in HUOP as openness and flexibility of schedules of visits, the presence of a companion in most hospital wards and ambience projects. Other provisions of PNH that involves changing process of management and include the discussion of the work and its consequences for the health of workers have not been prioritized. Thus the main difficulties for implementation of the HNP in this context stands out the model of centralized and vertical management, the absence of direct participation of management and segments of users in CH. Therefore, the management model change becomes an essential element to institute legitimate participation processes that include the different segments, aiming to establish more democratic practices that promote the necessary strategies for the implementation of the PNH in hospitals